2021
DOI: 10.1002/pon.5670
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Black and White: race and sexual identity as contributors to healthcare system distrust after breast cancer screening among US women

Abstract: Objective Healthcare system distrust (HCSD) has been linked to poor breast cancer outcomes. Previous HSCD analyses have focused on Black‐White disparities; however, focusing only on race ignores the complex set of factors that form identity. We quantified the contributions of race and sexual minority (SM) identity to HCSD among US women who had received breast cancer screening. Methods This cross‐sectional study used intersectionality decomposition methods to assess the degree to which racial and SM identity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Among studies that included SOGI as their intersection of focus ( n = 4), sexual minority women were less likely to engage in cancer prevention behaviors than heterosexual women 22,30‐32 . In several studies, these disparities were impacted by the intersection of the individual's other marginalized identity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among studies that included SOGI as their intersection of focus ( n = 4), sexual minority women were less likely to engage in cancer prevention behaviors than heterosexual women 22,30‐32 . In several studies, these disparities were impacted by the intersection of the individual's other marginalized identity.…”
Section: Resultsmentioning
confidence: 99%
“…21,23,28,29 Among studies that included SOGI as their intersection of focus (n = 4), sexual minority women were less likely to engage in cancer prevention behaviors than heterosexual women. 22,[30][31][32] In several studies, these disparities were impacted by the intersection of the individual's other marginalized identity. For example, in a study examining rates of mammography among women at the intersection of marginalized SOGI and racial identities, Agénor and colleagues reported that bisexual women had lower rates of mammography compared with heterosexual White women; however, the opposite pattern was noted among Black women.…”
Section: Pre-diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Population adoption of cancer screening tests 24‐27 is driven by several factors, many of which speak to the critical need to engage the population of potential users to understand their relevant attitudes and beliefs about the potential advantages of the innovation; the compatibility of the innovation with their experiences, values, and needs; the perceived complexity or challenges related to adoption of the innovation; and the visibility of the innovation among potential adopters 28,29 . It is critical to acknowledge and explore perceptions among patients about perceived harms from screening, such as overdiagnosis, false negatives, false positives, and invasive confirmatory tests, 30 especially for populations that may have had negative experiences or a lack of trust in the health care system 31 . Cancer advocacy organizations can serve as liaisons between screening test producers, researchers, and potential users to ensure the alignment of testing characteristics and processes with patients' needs and preferences.…”
Section: Framing the Futurementioning
confidence: 99%